In Situ Probing and Synthetic Control of Cationic Ordering in Ni‐Rich Layered Oxide Cathodes. Issue 3 (17th October 2016) - Zhao, Jianqing; Zhang, Wei; Huq, Ashfia; Misture, Scott T.; Zhang, Boliang; Guo, Shengmin; Wu, Lijun; Zhu, Yimei; Chen, Zonghai; Amine, Khalil; Pan, Feng; Bai, Jianming; et al.
Abstract : Ni‐rich layered oxides (LiNi1– x M x O2 ; M = Co, Mn, …) are appealing alternatives to conventional LiCoO2 as cathodes in Li‐ion batteries for automobile and other large‐scale applications due to their high theoretical capacity and low cost. However, preparing stoichiometric LiNi1– x M x O2 with ordered layer structure and high reversible capacity, has proven difficult due to cation mixing in octahedral sites. Herein, in situ studies of synthesis reactions and the associated structural ordering in preparing LiNiO2 and the Co‐substituted variant, LiNi0.8 Co0.2 O2, are made, to gain insights into synthetic control of the structure and electrochemical properties of Ni‐rich layered oxides. Results from this study indicate a direct transformation of the intermediate from the rock salt structure into hexagonal phase, and during the process, Co substitution facilities the nucleation of a Co‐rich layered phase at low temperatures and subsequent growth and stabilization of solid solution Li(Ni, Co)O2 upon further heat treatment. Optimal conditions are identified from the in situ studies and utilized to obtain stoichiometric LiNi0.8 Co0.2 O2 that exhibits high capacity (up to 200 mA h g −1 ) with excellent retention. The findings shed light on designing high performance Ni‐rich layered oxide cathodes through synthetic control of the structural ordering in the materials. Abstract : Ni‐rich layered oxides (LiNi1– x M x O2 ; M = Co, Mn, …) are promising high‐capacity cathodes for Li‐ion batteries; however, issues related to cationic disordering prevent their practical application. Here, in situ studies of synthesis reactions in preparing LiNiO2 and the Co‐substituted variant, LiNi0.8 Co0.2 O2 are made. Results from this work provide insights into synthetic control of cationic ordering and electrochemical properties of Ni‐rich layered oxide cathodes.